Effects of Flow Transport of the Ar Carrier on the Synthesis of ZnO Nanowires by Chemical Vapor Deposition - Choi, J; Seo, J; Cha, S; Kim, H; Kim, S; Park, Y; Kim, S; Yoo, J; Kim, J (2011)
ZnO nanowires were synthesized by the chemical vapor deposition (CVD) and heating of ZnO powders under Ar gas flow. The effect of the carrier gas (Ar) on the growth region inside the CVD chamber was systematically investigated. The transport of Zn vapor was assisted by the Ar gas flow, producing a spatial distribution of the growth of the ZnO nanowires (in this case, the longer nanowires grown in a certain region show better crystallinity). A simple model of a parabolic transport of Zn vapor (caused by the Ar flow) was, thus, proposed to explain these effects. Field-effect transistors (FETs) were also fabricated using ZnO nanowires and the device performance was determinded, showing a mobility of 20 cm2 V-1 s-1. © 2011 The Japan Society of Applied Physics.